Is a Mean Machine Better than a Dependable Drive? It’s Geared Toward Your Regulatory Focus - Scott, Graham G.; Sereno, Sara C.; O'Donnell, Patrick J. (Frontiers in Psychology, 2012)
While many studies have investigated the role of message-level valence in persuasive messages (i.e., how positive or negative message content affects attitudes), none of these have examined whether word-level valence can modulate such effects. We investigated whether emotional language used within persuasive messages influenced attitudes and whether the processing of such communications could be modulated by regulatory focus. Using a 2 (Message: Positive, Negative) × 2 (Words: Positive, Negative) design, participants read car reviews and rated each on a series of semantic differentials and product recommendations. While positive messages were always rated higher than negative ones, the valence of a message’s component words differentially impacted attitudes toward distinct aspects of the product. On promotion-focus features, messages containing negative words produced higher ratings; for prevention-focus aspects, those with positive words resulted in higher ratings. We argue that adopting a prevention- or promotion-focused stance can influence the interpretation of emotion words in relation to overall message comprehension.